Halal Certification Training and Assistance for Micro Business Actors through the Sihalal Platform in Blega Bangkalan - Ma'adi, Alan Su'ud; Karim, Busro (Jurnal Abmas Negeri (JAGRI), 2025)
The majority of products produced by micro business actors in Lomaer Village, Blega District, had not been halal-certified due to limited understanding and a lack of socialization, education, and assistance regarding halal certification. This condition encouraged the community service team to address the issue through a structured program. The purpose of this activity was to conduct training and mentoring on halal certification to help micro business actors improve their product quality and obtain halal certificates. The implementation methods included observation, idea planning, and a series of activities consisting of training and mentoring. The process began with the creation of a Business Identification Number (NIB), completion of business actor data onhttp://ptsp.halal.go.id, submission of facilitation registration data through the LPH Halal Center UTM, and registration of Sihalal business accounts. The outcomes of this program included increased awareness and understanding of the importance of halal certification, improved knowledge of the certification process among micro business actors, and their ability to identify halal and non-halal ingredients. As a result, five products from business actors in Lomaer Village successfully obtained halal certification.